Determination of Excessive Lifetime Cancer Risk for Workers Exposed to Natural Radioactive Materials in Various Equipment in Oil and Gas Sector - Abd, Saad M.; Naji, Nesreen B.; Majeed, Wasan Z.; Al-Mashhadani, Asia H. (Iraqi Journal of Science, 2024)
In the oil and gas sector of Basrah, natural radioactive materials are accumulated in various equipment like wellheads, pumps, and separation vessels, often manifested as scales, sludge, and other forms of waste. Without proper preventive measures, these accumulations pose significant risks to workers, the public, and the environment. This study aims to assess the lifelong cancer risks associated with production processes and the handling of resultant waste, be it scale sediments, sludge, or soil. Sample collection across different regions was based on the evaluation of production and storage facilities. Using a high-purity germanium detector (HPGe), activity concentrations of 226Ra, 232Th, and 40K were measured. These concentrations were then used with standard equations to determine indoor effective dose rates. The regional-weighted (the lifetime risk of cancer is a measure of the cumulative risk of cancer over a specific age range and has a clear, intuitive appear) average of the lifetime excessive cancer risk was varied between (0.40 to 0.11 ×10-3) for ELCRoutdoor, (3.13 to 0.86 ×10-3) for ELCRindoor and (0.97 to 3 ×10-3) for ELCRtotal, significantly surpassing the global average value of (0.29x10-3). This disparity underscores the heightened risk posed by these activities, emphasizing the urgent need for enhanced safety measures and regulatory oversight to safeguard human health and the environment.